The Effect Of Zikir On Psychological Conditions Student Medical - Lalibah Syafirah Mustika; Ida Royani; Nur Fadhillah Khalid (Jurnal EduHealth, 2024)
Psychological is defined as a condition that exists within a person that can affect the attitudes and behavior of that individual, medical students are more vulnerable to psychological problems due to the difficult educational process and the mismatch between reality and expectations. The process causes medical students to face various kinds of stressors such as a large academic load , time pressure , adjustment to the campus environment and relationships with peers. Dhikr is a mental state in which a person remembers Allah. The dhikr method can also be applied to the learning of the medical profession. The relationship between psychological conditions and religion , such as the relationship between religion as a belief and mental health , depends on how a person submits himself to the Most High. Positive feelings such as happiness , joy , contentment , or security will arise due to a similar nature of surrender.